Unexpected Findings of Duchenne Muscular Dystrophy in Prenatal Screening of Chromosome Abnormality Based on Cell-Free Fetal DNA - Zhao, Ganye; Liu, Lina; Shi, Panlai; Gu, Mingxin; Yang, Shaozhe; Kong, Xiangdong (American Journal of Perinatology, 2024)
This study aims to assess the feasibility of detecting and diagnosing Duchenne muscular dystrophy (DMD) during prenatal screening for chromosome abnormalities using cell-free fetal DNA extracted from peripheral blood samples of pregnant women.Two pregnant women identified as high risk through noninvasive prenatal testing (NIPT) underwent amniocentesis to obtain fetal cells. Subsequent fetal chromosomal karyotyping was conducted, and genomic DNA from fetal cells was extracted for copy number variation sequencing (CNV-Seq) analysis, complemented by multiplex ligation-dependent probe amplification (MLPA) to detect deletions or duplications within the DMD gene.NIPT results for the two samples indicated potential abnormalities involving chromosomes 21 and 18. However, karyotype analysis of the fetuses revealed no abnormalities. CNV-Seq identified deletions of 0.28 and 0.18 Mb within chromosome Xp21.1, encompassing the DMD gene, in each fetus. In family 1, MLPA results indicated a maternal heterozygous deletion spanning exons 12 to 41 in the DMD gene, while the fetus exhibited deletions in exons 12 to 41. In family 2, MLPA results confirmed normal DMD gene status in the pregnant woman's peripheral blood genomic DNA but revealed a fetal deletion spanning exons 48 to 52. Both fetuses were diagnosed with DMD and subsequently underwent termination.Abnormalities identified through NIPT necessitate further invasive prenatal diagnostic procedures. For cases involving chromosomal microdeletions or microduplications, a combination of karyotyping and CNV-Seq testing is essential for comprehensive diagnosis. NIPT followed by CNV-Seq may offer insights into large exon deletions within the DMD gene in specific instances.
Keywords: noninvasive prenatal testing; cell-free fetal DNA; copy number variation sequencing; Duchenne muscular dystrophy; prenatal diagnosis